Steps toward an Ecology of Markets: Markets as Evolving Computational Algorithms - Rosenberg, James (Sociological theory, 2025)
Approaches to the study of markets in economic sociology have been converging with an approach to markets found in the field of evolutionary economics. In this view, markets are treated as sets of rules that facilitate the exchange of goods and information. These rule sets can be modeled and formalized as evolving computational algorithms situated in an ecology of human beings. I demonstrate this convergence and show that closer dialogue between these fields could contribute to the development of a framework for classifying diverse market forms, studying their change over time, and accounting for the causal mechanisms by which they produce varied outcomes. This would provide tools with which to grasp empirical phenomena of interest to economic sociologists, political economists, and policy scholars that elude existing sociological approaches. But it would also represent a first step toward a grander project: a “natural history of markets.”